'The circle of life': The role of life course in understanding job quality. (February 2023) - Belardi, Susan; Knox, Angela; Wright, Chris F
This article seeks to examine the role of life course in understanding job quality. It uses a qualitative case study analysis of Australian restaurants and reveals how chefs at different life stages can subjectively perceive the same objective job characteristics differently. The findings extend pre-existing knowledge by demonstrating how workers' subjective perceptions of job quality are shaped by their life stages.